A high trans-zeatin nucleoside concentration in corms may promote the multileaf growth of Amorphophallus muelleri - Xue, Zhiqin; Huang, Feiyan; Liu, Jiani; Ke, Yanguo; Wei, Huanyu; Gao, Penghua; Qi, Ying; Yu, Lei (Frontiers in Plant Science, 2022)
Amorphophallus muelleri has a multileaf growth pattern different from that of other konjacs; however, the hormonal mechanism underlying this phenomenon is not clear. In this study, the levels of hormones closely related to dormancy and germination, including five types of cytokinin, indole-3-acetic acid, and abscisic acid, were measured and assessed in combination with the expression of related genes in samples of A. muelleri from different tissues encompassing the growth cycle. Except for kinetin, the content of all types of cytokinins was significantly higher in corms than in leaves, especially in the second leaf sprouting stage, where the content of trans-zeatin riboside (tZR) in corms increased more than 5000-fold, while the CYP735A gene in the tZR biosynthesis pathway also showed high expression during the same period. In addition, the indole-3-acetic acid content in the corms also considerably increased during the second leaf sprouting. We speculate that the increase in auxin content may be induced by elevated cytokinin levels. This study showed the changes in major hormones involved in second bud germination and the transcriptional regulation during the growth cycle in A. muelleri. These results will assist in the understanding of the effect of hormone change on the multileaf growth pattern.